Hello / Faryna Mohd Khalis - Mohd Khalis, Faryna (Faculty of Art and Design, 2021)
“Hello” is synonymous with Hi, which people often use for greeting or to begin a phone conversation. However, in my version, Hello is different because in this artwork Hello represents my friend’s cat's name, Hello. Hello is five-year-old female cat which belongs to my friend whose allergy towards cats is rather bad. Prior to this, there has never been any cat in her house. This is her first time having a cat. I bet now she loves her Hello so much. I do love cats so much and I have one at home too. But Hello is different; besides her catchy name she has unique characteristics too. Sometimes I think she acts like a human. She loves coconut drinks, yogurt, and cheese. I purposely portray her as a diva character with a crown, flowers and I place her in a mirror-like frame because Hello loves to look at her reflection in the mirror too!. Personally, this artwork is special to me because it is my first time choosing an animal as a subject matter since my favourite actually lies in portraiting. Plus, it is also my first time using an Ipad and I am rather happy in my first attempt at using this App as my digital toy to produce this artwork entitled “Hello”.